MAKNA TEOLOGIS DAN EKSISTENSIAL DARI "SEBAB PADA HARI ENGKAU MEMAKANNYA, PASTILAH ENGKAU MATI": (KEJADIAN 2:17) - Erick Hetharia Yohanes; Dicky Kancil (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
This study analyzes the theological and existential meaning of God's warning in Genesis 2:17: "For on the day you eat of it, you shall surely die." This verse holds profound dimensions concerning the relationship between humanity, sin, and God. Theologically, this warning emphasizes the consequences of sin, which result in death—physical, spiritual, and eternal. Sin is understood as a violation of God's authority, disrupting the relationship between humanity and the Creator and causing separation from Him. Existentially, this verse reflects human freedom accompanied by moral responsibility, as well as the consequences of misusing free will, which lead to suffering and alienation. The death referred to in Genesis 2:17 is not merely the cessation of physical life but also the disruption of the spiritual connection between humanity and God. This study further highlights how this warning serves as a foundation for understanding the need for restoration through God’s redemptive work in Christ. In conclusion, Genesis 2:17 teaches the profound consequences of sin, the importance of obedience to God, and the hope for restored relationships through His grace.